A cross-sectional study on the impact of physical exercise on mobile phone addiction: the chain mediating role of perceived stress and self-acceptance - Ding, Zhen; Qi, Xinru; Fang, Tianle; Xiao, Lishun; Yin, Dehui; Sun, Zhiming (Frontiers in Psychology, 2025)
ObjectiveThis study aims to explore the potential pathways underlying the association between physical exercise and mobile phone addiction among university students, with particular attention to the possible sequential mediating roles of perceived stress and self-acceptance. The goal is to generate insights that may inform future research and contribute to a deeper understanding of psychological health in higher education settings.MethodsThis cross-sectional study employed a convenience sampling method to survey 1,392 undergraduate students from Xuzhou Medical University. The study utilized the Physical Activity Rating Scale (PARS-3), the Mobile Phone Addiction Tendency Scale (MPATS), the Perceived Stress Scale (PSS), and the Self-Acceptance Questionnaire (SAQ). Data were analyzed using SPSS 27.0 and the PROCESS macro (Model 6) to conduct descriptive statistics, correlation analysis, and mediation analysis.ResultsPhysical exercise was significantly negatively correlated with mobile phone addiction (r = −0.293, p < 0.01) and perceived stress (r = −0.326, p < 0.01), and positively correlated with self-acceptance (r = 0.408, p < 0.01). The total effect of physical exercise on mobile phone addiction was −0.291, and the direct effect was −0.135. The indirect effect through perceived stress was −0.118 (95% CI: [−0.149, −0.090]), through self-acceptance was −0.024 (95% CI: [−0.041, −0.010]), and the chain mediating effect through both perceived stress and self-acceptance was −0.014 (95% CI: [−0.024, −0.006]). All indirect effects were statistically significant, indicating that physical exercise significantly affects mobile phone addiction through these pathways.ConclusionPhysical exercise has been found to show a negative association with mobile phone addiction among university students. This association appears to involve both direct links and indirect pathways through lower levels of perceived stress and higher levels of self-acceptance, suggesting a potential chain mediating relationship. These findings contribute to a deeper understanding of the complex interplay between physical activity, psychological factors, and mobile phone use behaviors in university populations.